Is the Pharmacokinetic Profile of a First Anti-TNF Predictive of the Clinical Outcome and Pharmacokinetics of a Second Anti-TNF?. Issue 9 (26th April 2018) - Roblin, Xavier; Vérot, Céline; Paul, Stéphane; Duru, Gérard; Williet, Nicolas; Boschetti, Gilles; Del Tedesco, Emilie; Peyrin-Biroulet, Laurent; Phelip, Jean Marc; Nancey, Stéphane; Flourie, Bernard
Abstract: Aim: The aim of this study was to evaluate prospectively the clinical outcomes and pharmacokinetics of a second anti-TNF according to the pharmacokinetics of the first anti-TNF in patients with inflammatory bowel disease (IBD). Methods: In patients in loss of response (LOR) to a first optimized anti-TNF and switched to a second anti-TNF, pharmacokinetics of anti-TNF were measured at the switch time, 30 weeks later, at the time of LOR, or at the end of the study (102 weeks). Results: At the switch time, patients (n = 59) belonged to 4 groups according to the pharmacokinetics of the first anti-TNF: group 1 (n = 18), therapeutic trough levels; group 2 (n = 13) undetectable trough levels with antibodies against anti-TNF; group 3 (n = 13) without antibodies against anti-TNF; and group 4 (n = 15) subtherapeutic trough levels. After switching, the failure rates at week 30 and during the follow-up were as follows, respectively: in group 1 with therapeutic levels, 50% and 78%, despite therapeutic levels of the second anti-TNF in 83% of cases; in group 2 with undetectable levels and antibodies, 15% and 69% with undetectable levels of the second anti-TNF and antibodies in 85% of cases; in group 3 with undetectable levels without antibodies, 0% and 31% with therapeutic levels in 77% of cases; in group 4 with subtherapeutic levels, 13% and 33% with therapeutic levels in 73% of cases. Clinical remission rates were significantly lower ( P ≤ 0.05) in groups 1 and 2 with therapeutic or undetectable levels with antibodies than in the 2 other groups. Conclusion: In the case of LOR with therapeutic levels of the first anti-TNF or undetectable levels with antibodies, the switch to a second anti-TNF results in pharmacokinetic profile similar to the first one and again in LOR in most of the patients.